Impaired insulin signaling affects renal organic anion transporter 3 (Oat3) function in streptozotocin-induced diabetic rats - Anusorn Lungkaphin (2018)
Organic anion transporter 3 (Oat3) is a major renal Oats expressed in the basolateral membrane of renal proximal tubule cells. We have recently reported decreases in renal Oat3 function and expression in diabetic rats and these changes were recovered after insulin treatment for four weeks. However, the mechanisms by which insulin restored these changes have not been elucidated. In this study, we hypothesized that insulin signaling mediators might play a crucial role in the regulation of renal Oat3 function. Experimental diabetic rats were induced by a single intraperitoneal injection of streptozotocin (65 mg/kg). One week after injection, animals showing blood glucose above 250 mg/dL were considered to be diabetic and used for the experiment in which insulin-treated diabetic rats were subcutaneously injected daily with insulin for four weeks. Estrone sulfate (ES) uptake into renal cortical slices was examined to reflect the renal Oat3 function. The results showed that pre-incubation with insulin for 30 min (short term) stimulated [3H]ES uptake into the renal cortical slices of normal control rats. In the untreated diabetic rats, pre-incubation with insulin for 30 min failed to stimulate renal Oat3 activity. The unresponsiveness of renal Oat3 activity to insulin in the untreated diabetic rats suggests the impairment of insulin signaling. Indeed, pre-incubation with phosphoinositide 3-kinase (PI3K) and protein kinase C zeta (PKCζ) inhibitors inhibited insulin-stimulated renal Oat3 activity. In addition, the expressions of PI3K, Akt and PKCζ in the renal cortex of diabetic rats were markedly decreased. Prolonged insulin treatment in diabetic rats restored these alterations toward normal levels. Our data suggest that the decreases in both function and expression of renal Oat3 in diabetes are associated with an impairment of renal insulin-induced Akt/PKB activation through PI3K/PKCζ/Akt/PKB signaling pathway. © 2014 Lungkaphin et al.